Amphetamines in the treatment of Parkinson's disease. Issue 3 (March 1975) - Parkes, J D; Tarsy, D; Marsden, C D; Bovill, K T; Phipps, J A; Rose, P; Asselman, P
Abstract : Twenty-two patients with Parkinsonism were treated with levoamphetamine and 12 of these with dextroamphetamine. Levoamphetamine resulted in a significant improvement in disability from Parkinsonism, although the reduction in total disability, tremor, akinesia, and rigidity scores was slight (ca 20 percent). Dextroamphetamine in lower dosage also reduced disability by some 17 percent. The most disabled patients, including those also on levodopa, showed the greatest response to amphetamines. Previously, amphetamines have been reported to be a selective treatment for the oculogyric crises of post-encephalitic Parkinsonism. Amphetamines are thought to cause the release of catecholamines from central neurones. Their action in Parkinson's disease may be limited because of pre-existing striatal dopamine deficiency. Side-effects of amphetamines, anorexia, and CNS stimulation are different from those caused by levodopa in patients with Parkinson's disease.